2010
DOI: 10.1128/cvi.00530-09
|View full text |Cite
|
Sign up to set email alerts
|

Interacting Roles of Immune Mechanisms and Viral Load in the Pathogenesis of Crimean-Congo Hemorrhagic Fever

Abstract: Until now, the pathogenesis of Crimean-Congo hemorrhagic fever (CCHF) has not been well described. However, it has been hypothesized that it could be a result of the direct injury of virus-infected tissues in combination with the indirect effects of host immune responses, including cytokines. To shed more light on the role of viral load and cytokines, differential influences of CCHF virus (CCHFV) RNA load, antibody response, and cytokine production on severity and outcome of the disease were studied in sera of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
147
2
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(165 citation statements)
references
References 42 publications
12
147
2
4
Order By: Relevance
“…Similar observations have been made in Kosovo and Albania (Duh et al, 2007;Papa et al, 2006). Studies in both countries have shown that serum viral load is directly related to disease severity (Ergonul et al, 2006b;Saksida et al, 2010). In Kosovo, fatally infected patients had the highest levels of TNF-a, IFN-c and IL-10, while the Turkish study found that fatality was correlated with elevated IL-6 and TNF-a, but not IL-10.…”
Section: Predictors Of Survival or Deathsupporting
confidence: 62%
See 1 more Smart Citation
“…Similar observations have been made in Kosovo and Albania (Duh et al, 2007;Papa et al, 2006). Studies in both countries have shown that serum viral load is directly related to disease severity (Ergonul et al, 2006b;Saksida et al, 2010). In Kosovo, fatally infected patients had the highest levels of TNF-a, IFN-c and IL-10, while the Turkish study found that fatality was correlated with elevated IL-6 and TNF-a, but not IL-10.…”
Section: Predictors Of Survival or Deathsupporting
confidence: 62%
“…Early studies in South Africa found that most patients who went onto survive the disease had detectable anti-CCHFV IgM by day 7 and IgG by day 7-9 of illness, while no response was detected in fatally infected individuals (Burt et al, 1994;Shepherd et al, 1989c;van Eeden et al, 1985b). The correlation of antibody responses with survival has been demonstrated more recently in patients in Turkey and Kosovo (Ergonul et al, 2006a;Saksida et al, 2010).…”
Section: Predictors Of Survival or Deathmentioning
confidence: 99%
“…A direct correlation between the severity of disease for CCHF and a high viral load had already been observed in several patient studies (9,14,33), although the molecular mechanisms underlying this observation were not further elucidated. We tentatively speculate that the mechanism underlying the correlation between high viral load and disease severity in patients could be caused in part by the virus-enhanced endothelial cell activation, followed by excessive inflammatory reactions and leukocyte recruitment.…”
Section: Fig 2 Activation Of Endothelial Cells Is Virus Dose Dependmentioning
confidence: 99%
“…Elevated serum levels of the proinflammatory cytokines interleukin 6 (IL-6) and TNF-␣ were correlated with CCHF disease severity in several patient studies, and IL-8 levels were increased in a fatal case of CCHF in Greece (16,28,29,33). These cytokines were also released from CCHFV-infected dendritic cells (DCs) and macrophages (11,30).…”
mentioning
confidence: 92%
See 1 more Smart Citation